Effects of unilateral, bilateral, and combined unilateral+bilateral complex resistance training on bench press and squat strength in adolescent boxers - Yang Liu; Yang Liu; Xiuxia Liu; Jiaxian Geng (Frontiers in Physiology, 2024)
Objective: To assess the effects of 8 weeks of unilateral (UNI), bilateral (BI), and combined unilateral + bilateral (UNI + BI) resistance training on bench press and squat strength in adolescent boxers.Methods: Using the Gym Aware linear accelerometer, free-weight squat and bench press strength exercises were evaluated after an 8-week training intervention. Thirty adolescent boxers were randomly assigned to three groups: UNI, height: 1.73 ± 0.08 m, weight: 55.42 ± 5.85 kg; UNI + BI, height: 1.7 ± 0.06 m, weight: 54.73 ± 5.33 kg; and BI, height: 1.74 ± 0.06 m, weight: 59.67 ± 8.39 kg. Each group followed their designated UNI/BI/UNI + BI compound resistance training protocols, and the effects of 8 weeks of single-sided and bilateral intervention training on the performance of free-weight squat and bench press exercises at 30%, 50%, and 80% of 1-repetition maximum (1RM) were evaluated.Results: Significant improvements were observed in the 30% 1RM, 50% 1RM, and 80% 1RM outcomes for both squat and bench press exercises before and after the interventions (p < 0.05, p < 0.01). In the intergroup comparison, GymAware measurements revealed that the UNI and UNI + BI groups exhibited superior peak power values for squat and bench press exercises at 30% 1RM compared to the BI group.Discussion: UNI and UNI + BI training led to significantly higher output power values in bench press and squat exercises at 30% 1RM compared to the BI training group.